Análise semântico-pragmática de conceitos na tributação do metaverso - Souza, Cecilia Priscila de (2023)
If language creates reality and the Metaverse is an environment undeniably created by language - in the strictest sense of the term -, the tax analysis of the theme aims which are the conditions for a legal system to reach the manifestations of richness that can compose the materiality of taxes. As the development of the work is based on the Semantic Logical Constructivism, it was necessary to develop some concepts – like legal or foundational ones – for the system, in order to equate them in the physical world and in the new virtual world, currently called Metaverso. Based on the similarities between them, it is possible to talk about society, the legal system and then deal with their taxation, since, with the hypercomplexity of the way in which social relations are presented, it is essential to recognize the evolution of concepts and the way in which they relate to synchronic and diachronic realities, once the normative system itself sets limits for the incidence on situations that are constituted outside the physical environment